(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article examines the role of formulaic sequences in language learning, focusing on their importance in enhancing fluency, comprehension, and overall linguistic competence. It provides a review of relevant literature, discusses research methods for studying formulaic language, and explores empirical results highlighting its benefits for learners. The article concludes with practical recommendations for language instruction.